The risks for adolescents of negatively biased self‐evaluations of social competence: The mediating role of social support. Issue 6 (14th June 2014) - Bédard, Karine; Bouffard, Thérèse; Pansu, Pascal
ABSTRACT: This study conducted among 544 adolescents ( M = 15.1 years, SD = .82) examined whether perceived social support from parents and peers mediated the relationship between biased self‐evaluations of social competence and internalizing problems. The results showed negative links between bias in self‐evaluation and depressive symptoms, social anxiety and social avoidance. Bias in self‐evaluation of social competence was more strongly related to perceived peer support than perceived parental support. Gender differences were observed in the mediating role of social support. Among boys, parental support was a partial mediator only of the link between bias in self‐evaluation and depressive symptoms. While perceived peer support was a partial mediator of the links between bias in self‐evaluation and depressive symptoms, social anxiety and social avoidance in girls, this was the case only for social avoidance in boys. These findings suggest that girls may show vulnerability to peer emotional support at an earlier age than boys.